The Interview for Decisional Abilities (IDA): a tool to assess the decisional capacity of abused and neglected older adults. Issue 3 (27th May 2019) - Abrams, Robert C.; Ansell, Pamela; Breckman, Risa; Karlawish, Jason; Lachs, Mark; Holt-Knight, Deborah; Needell, Nancy; Rogers, Geoffrey; LoFaso, Veronica
ABSTRACT: We present the Interview for Decisional Abilities (IDA), a semi-structured tool for use by adult protective services (APS) workers as part of their comprehensive assessments of clients. The IDA was created in response to a Federal mandate to standardize the procedures and competencies of APS agencies with a view to improving client assessments and facilitating cross-jurisdictional research on adult mistreatment. The proximal aim of the IDA is to guide workers in gathering information on the ability of suspected victims of adult mistreatment to make decisions about the risks they face.